A mini review of additive manufacturing in medical, automotive, and construction applications - Heidari, Fatemeh; Gholizadeh, Saeid (Journal of Composites and Compounds, 2024)
Additive manufacturing (AM), commonly known as 3D printing, is a transformative approach to producing complex geometries that uses digital models to directly layer materials. Compared to conventional subtractive methods, AM uses minimal material waste and reduces production time, thereby lowering manufacturing costs. These advantages show the growing demand for 3D printers, especially where precision, customization, and efficiency are important. In this brief review, we focus on AM applications in medicine, where it enables patient-specific solutions; in the automotive sector, where it supports lightweight and optimized designs; and in construction, where it contributes to sustainable and rapid development. This review presents AM as a versatile technology that is reshaping multiple industries.